Characterization of human sperm N-acetylglucosaminidase - Perez Martinez, Silvina Laura (2008)
N-acetylglucosaminidase (NAG) is particularly active in mammalian spermatozoa and appears to be involved in fertilization. Although it is assumed that this enzyme is acrosomal, previous results from our laboratory suggest the presence of NAG at the sperm plasma membrane level. The present study attempted to analyse the subcellular distribution of this enzyme in human spermatozoa. Sperm were incubated under different conditions and NAG activity measured in the soluble extracts and cell pellets using a specific fluorometric substrate. A significant proportion of NAG activity was released when sperm were incubated in culture medium, suggesting a weak association with the plasma membrane. This location was confirmed by western blot analysis of plasma membrane fractions and immunofluorescence on non-permeabilized sperm, which showed a positive signal mainly on the acrosomal domain. The distribution of NAG activity between plasma membrane and acrosome was analysed after cell disruption by freezing and thawing. Triton X-100 stimulated sperm and epididymal NAG activity but not the enzyme obtained from other sources. In addition, biotinylated human recombinant NAG was able to bind to human sperm. Finally, after sperm incubation under capacitating conditions, NAG total activity increased and the sperm enzyme lost its ability to be stimulated by Triton X-100. The possible connection of these results with sperm maturation, capacitation and NAG participation in primary binding to the zona pellucida, was discussed.